2022
DOI: 10.4102/ajlm.v11i1.1614
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing accreditation outcomes for medical laboratories on the Strengthening Laboratory Management Toward Accreditation programme in Kenya via a rapid results initiative

Abstract: Background: Since 2010, Kenya has used SLIPTA to prepare and improve quality management systems in medical laboratories to achieve ISO 15189 accreditation. However, less than 10% of enrolled laboratories had done so in the initial seven years of SLMTA implementation.Objective: We described Kenya’s experience in accelerating medical laboratories on SLMTA to attain ISO 15189 accreditation.Methods: From March 2017 to July 2017, an aggressive top-down approach through high-level management stakeholder engagement f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
2
1
0
1
Order By: Relevance
“…However, there are limited publications addressing how laboratories involved in SLMTA sustain their achieved quality performance and progress towards accreditation. A study conducted in Kenya, seven years after the SLMTA phase-out, reported outcomes similar to our study [ 30 ]. The interventions of training of personnel in LQMS, mentorship, and assessments, as seen in the group two laboratories’ interventions in our study, also led to positive outcomes in Kenya [ 30 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, there are limited publications addressing how laboratories involved in SLMTA sustain their achieved quality performance and progress towards accreditation. A study conducted in Kenya, seven years after the SLMTA phase-out, reported outcomes similar to our study [ 30 ]. The interventions of training of personnel in LQMS, mentorship, and assessments, as seen in the group two laboratories’ interventions in our study, also led to positive outcomes in Kenya [ 30 ].…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted in Kenya, seven years after the SLMTA phase-out, reported outcomes similar to our study [ 30 ]. The interventions of training of personnel in LQMS, mentorship, and assessments, as seen in the group two laboratories’ interventions in our study, also led to positive outcomes in Kenya [ 30 ]. A recently published study, collecting data spanning seven years starting in 2013, on medical laboratories implementing quality management systems in Sub-Sahara Africa, indicates that a national framework including laboratory policies and a strategic planning is likely to facilitate ISO 15,189 standard accreditation [ 31 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, accreditation preparedness can be attained from a lower star level depending on resources and dedication. [ 16 , 17 ]. SLIPTA certificates are not designed to recognise technical competence for any test.…”
Section: Introductionmentioning
confidence: 99%
“…Із зарубіжних авторів варто відзначити такі роботи як: Sartori S., Pfeifer T., Crossman M., KBr K. canuto, Ferraris, Gallorini M., Moretti Laura, Peisino, Ferrero C., Balsamo A., Pogliano U. [6], GROUP EA-LC, Ferrero C. [7], Karaaoui Abdul, Assaf Nada [8], Makokha Ernest, Ondondo Raphael, Kimani Daniel, Gachuki Thomas, Basiye Frank, Njeru Mercy, Junghae Muthoni, Downer Marie, Umuro Mamo, Mburu Margaret, Mwangi Jane [9], Oliver Anthony [10], Grochau Ines, Leal Dayane, Caten Carla [11], Tanhehco Yvette, Schwartz Joseph [12], Richter Karol, Erard Luc, Ferrero C., Cofrac Gabriel, Crossman Mike [13], Moreno Silva Patricia, Uribe Ardila Alfredo [14], El Marsafawy Hesham, Roy Rumpa, Ali Fahema [15], Caten Carla [16] [17,18,19] Процес акредитації має кілька переваг [17], як було зазначено раніше, однак найважливішою з них є переваги для клієнта/клієнтів, які використовують послуги лабораторії. Перевагами можуть бути підвищена довіра клієнтів до звітів про випробування, виданих лабораторією, і це призводить до потенційного зростання бізнесу завдяки підвищенню довіри клієнтів і задоволеності.…”
unclassified